2019
DOI: 10.1590/1806-9479.2019.187826
|View full text |Cite
|
Sign up to set email alerts
|

Agricultura familiar e alimentação escolar: desafios para o acesso aos mercados institucionais em três municípios mineiros1Este artigo resulta de pesquisa apoiada pela Fapemig.

Abstract: Resumo A compra da agricultura familiar para a alimentação escolar traz variadas potencialidades para o desenvolvimento local sustentável, para a valorização de uma alimentação saudável e que respeite a cultura alimentar local, e para a reconexão entre produtores e consumidores. Por outro lado, traz diversos desafios frente à complexidade das relações entre agricultura familiar, alimentação escolar e poder público. Esse artigo tem como objetivo analisar os principais desafios para a venda da agricultura famili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
17

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 11 publications
(5 reference statements)
0
6
0
17
Order By: Relevance
“…The availability of food from family farms was highlighted as one of the major criteria in 5 of the 21 municipalities analyzed. Studies have shown that irregular supply of food, inadequate hygiene and sanitary conditions, and lack of farmers or coordination between sectors are the major factors affecting the purchase of food from family farms [34][35][36][37][38]. On the other hand, over the years, municipalities have been able to overcome such barriers and increase the acquisition of food from family farms [34,36,39,40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The availability of food from family farms was highlighted as one of the major criteria in 5 of the 21 municipalities analyzed. Studies have shown that irregular supply of food, inadequate hygiene and sanitary conditions, and lack of farmers or coordination between sectors are the major factors affecting the purchase of food from family farms [34][35][36][37][38]. On the other hand, over the years, municipalities have been able to overcome such barriers and increase the acquisition of food from family farms [34,36,39,40].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, over the years, municipalities have been able to overcome such barriers and increase the acquisition of food from family farms [34,36,39,40]. For advances in this regard, it is essential that actors from the different sectors involved -from those associated with policy-making to those related to the execution, monitoring, and evaluation of actions -communicate and work together toward a similar goal [35,36,41]. An example of such collaboration is the planning of school menus in accordance with food availability, as identified in the current study [34,42].…”
Section: Discussionmentioning
confidence: 99%
“…This is the case also with family farming, which sales to the PNAE are not guaranteed. The reasons alleged by the EE for not buying food from producers of small local properties, even before the pandemic period, are: insufficient production, difficulty in distribution and delivery logistics, problems with documentation and failure to meet the criteria of the public call [29][30][31][32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…As cooperativas e associações, devido as suas condições de organização e posse de maior capital de giro, possibilitam uma estrutura de armazenamento e transporte mais adequada, possuem menor dificuldade em atender aos aspectos Research, Society and Development, v. 10, n. 4, e26610414028, 2021 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v10i4.14028 burocráticos, favorecendo a capacidade de oferta de forma regular ao programa (Cunha, 2015). Ao priorizar os grupos formais de agricultores, o PNAE contribui no fortalecimento de organizações dos pequenos produtores e favorece maior inserção destes no mercado institucional, contribuindo para a garantia da SAN dessas famílias (Assis et al, 2019) e fomento da economia local. Baccarin et al (2017) ressaltaram a importância das cooperativas na intermediação da participação dos agricultores no PNAE, mediante cooperação em diversos aspectos para o acesso à política.…”
Section: Nº Contratosunclassified